Development of an Assessment of Quantitative Literacy for Miami University - Rose Marie Ward; Monica C. Schneider; James D. Kiper (Numeracy, 2011)
Quantitative Literacy is a competence as important as general literacy; yet, while writing requirements are seemingly ubiquitous across the college curriculum, quantitative literacy requirements are not. The current project provides preliminary evidence of the reliability and validity of a quantitative literacy measure suitable for delivery online. A sample of 188 undergraduate students from Miami University, a midsize university in the midwestern U.S., participated in the current study. Scores on the measure, were inversely related to statistical/mathematical anxiety measures, directly related to subjective assessment of numeracy, and did not differ across gender or year in school. The resulting measure provides a reasonable tool and method of assessing quantitative literacy at a midsize university.